Biosynthesis and Ether‐Bridge Formation in Nargenicin Macrolides. Issue 12 (11th February 2019) - Pidot, Sacha J.; Herisse, Marion; Sharkey, Liam; Atkin, Liselle; Porter, Jessica L.; Seemann, Torsten; Howden, Benjamin P.; Rizzacasa, Mark A.; Stinear, Timothy P.
Abstract: The nargenicin family of antibiotics are macrolides containing a rare ether‐bridged cis ‐decalin motif. Several of these compounds are highly active against multi‐drug resistant organisms. Despite the identification of the first members of this family almost 40 years ago, the genetic basis for the production of these molecules and the enzyme responsible for formation of the oxa bridge, remain unknown. Here, the 85 kb nargenicin biosynthetic gene cluster was identified from a human pathogenic Nocardia arthritidis isolate and this locus is solely responsible for nargenicin production. Further investigation of this locus revealed a putative iron‐α‐ketoglutarate‐dependent dioxygenase, which was found to be responsible for the formation of the ether bridge from the newly identified deoxygenated precursor, 8, 13‐deoxynargenicin. Uncovering the nargenicin biosynthetic locus provides a molecular basis for the rational bioengineering of these interesting antibiotic macrolides. Abstract : Building (oxa‐) bridges : The biosynthetic locus for the potent antibiotic nargenicin was identified from a human pathogenic Nocardia strain. Gene inactivation studies identified an unusual dioxygenase responsible for ether‐bridge formation, and the removal of the ether bridge abolished nargenicin antibiotic activity.